Intracellular Mn mobility and differential response to H2O2 accumulation explain the susceptibility of litchi cultivars to dark pericarp disease - Huilin, Liu (Plant physiology and biochemistry : PPB, 2025)
Copyright © 2025. Published by Elsevier Masson SAS.